PENGARUH TRANSPARANSI AKUNTABILITAS PARTISIPASI MASYARAKAT DAN KOMPETENSI APARAT DESA TERHADAP PENGELOLAAN DANA DESA - Dennyca Hendriyanto Nugroho; Febra Robiyanto (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2023)
This study aims to examine the effect of transparency, accountability, community participation, and competence of village officials on village fund management in villages in Bae District, Kudus Regency. This type of research is quantitative research using descriptive methods. The sampling technique uses purposive sampling with the number of respondents as many as 10 people per village, so that the total respondents are 100 people. The data analysis method used is multiple linear regression analysis using the SPSS program version 25. Based on the results of the research conducted, it shows that transparency, accountability, community participation, and competence of village officials simultaneously have a significant effect on village fund management. Meanwhile, partially, transparency does not have a significant effect on village fund management. Accountability has a significant positive effect on village fund management. Community participation has a significant positive effect on village fund management, and the competence of village officials has a significant positive effect on village fund management